KNOWLEDGE OF THE POPULATION SERVED BY BASIC HEALTH UNITS IN THE NORTHEAST REGION OF ANÁPOLIS, GOIÁS, ABOUT SYPHILIS - Moraes, Letícia Karen de; Mattos, Amanda Silva de; Roberto, Giovanna Luiza Silva; Dias, Lorrayne Leite; Borges, Mariana Rodrigues; Arruda, Jalsi Tacon; Moura, Léa Resende (CIPEEX, 2025)
Brazil is experiencing a syphilis epidemic with a growing number of cases. Therefore, the challenge of identifying, treating, and guiding the population to adopt preventive measures is one of the priorities for public health. Thus, this study evaluated the level of knowledge about syphilis in the population served by Basic Health Units (BHUs) in the northeastern region of Anápolis, Goiás. This is an observational, cross-sectional, and descriptive study in which a questionnaire was administered to individuals seeking care at the BHUs during 2023, and an informational booklet was provided. Data from 45 participants were collected, of whom 51.11% were female, 42.22% were married, and 48.89% had a high school education. Regarding knowledge, 71.11% stated that they knew what syphilis is. As for the etiological agent of the disease, 31.11% responded that syphilis is caused by bacteria. Regarding transmission, 82.2% responded that it is transmitted through sexual contact. It was concluded that the majority of study participants were women between the ages of 18 and 39. Most were incorrect about the etiological agent, but they were correct about the mode of transmission. Furthermore, most correctly identified the initial clinical manifestation of the disease and recognized that the main method of prevention is the use of condoms (84.44%). However, when analyzing risk behavior, 6.67% of the sample had sexual relations with non-steady partners in the last six months, of which 33.33% did not use condoms. Accordingly, this study may contribute to more targeted health promotion interventions in this region, aiming to disseminate knowledge to this population.